2016
DOI: 10.1073/pnas.1525055113
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone interactions with Mycobacterium tuberculosis gyrase: Enhancing drug activity against wild-type and resistant gyrase

Abstract: Mycobacterium tuberculosis is a significant source of global morbidity and mortality. Moxifloxacin and other fluoroquinolones are important therapeutic agents for the treatment of tuberculosis, particularly multidrug-resistant infections. To guide the development of new quinolone-based agents, it is critical to understand the basis of drug action against M. tuberculosis gyrase and how mutations in the enzyme cause resistance. Therefore, we characterized interactions of fluoroquinolones and related drugs with W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(131 citation statements)
references
References 47 publications
6
125
0
Order By: Relevance
“…In this study, we found a relatively high prevalence of mutations in QRDR-A, at 96.7% among isolates examined, and the most frequent mutations occurred in GyrA at D94 (72.7%). Because the D94 residue, which anchors the water-magnesium ion bridge with a conserved C3/C4 keto acid moiety of quinolones, plays an important role in stabilizing the quinolone molecule in the QBP, an amino acid substitution at this position will exaggerate the deleterious effect of the binding between most quinolones and DNA gyrase (41,42). In addition, the high frequency of D94 mutations in clinical isolates from pre-XDR and XDR-TB may be due to the positive epistasis between D94 mutations and mutations conferring rifampin resistance leading to the progression of MDR-TB to XDR-TB (43).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found a relatively high prevalence of mutations in QRDR-A, at 96.7% among isolates examined, and the most frequent mutations occurred in GyrA at D94 (72.7%). Because the D94 residue, which anchors the water-magnesium ion bridge with a conserved C3/C4 keto acid moiety of quinolones, plays an important role in stabilizing the quinolone molecule in the QBP, an amino acid substitution at this position will exaggerate the deleterious effect of the binding between most quinolones and DNA gyrase (41,42). In addition, the high frequency of D94 mutations in clinical isolates from pre-XDR and XDR-TB may be due to the positive epistasis between D94 mutations and mutations conferring rifampin resistance leading to the progression of MDR-TB to XDR-TB (43).…”
Section: Discussionmentioning
confidence: 99%
“…1A) increases activity against mycobacteria, particularly resistant mutants (18)(19)(20). Indeed, moxifloxacin, along with a more active C8-methyl derivative, retains high inhibitory activity against purified Mtb gyrase even when the enzyme contains commonly acquired fluoroquinoloneresistance substitutions [as described in the accompanying paper by Aldred et al (21)]. In another example, quinazolinediones (diones) have been shown to have an ability to bypass existing resistance within mycobacteria and other bacterial species (20,(22)(23)(24).…”
Section: Significancementioning
confidence: 99%
“…One notable, watermediated magnesium-ion contact is with Asp94 of GyrA; this interaction likely accounts for why many substitutions at Asp94 lead to drug insensitivity in fluoroquinolone-resistant laboratory and clinical strain isolates (11,47) (see also ref. 21). …”
Section: A90smentioning
confidence: 99%
“…Unfortunately, despite this dual targeting, the rise of clinical resistance to FQs, most commonly by mutation in the conserved GyrA S83 and D87 amino acid residues (Escherichia coli numbering), has compromised the use of this important class of antibiotics, especially in infections caused by Gram-positive and -negative pathogens (13) and in MDR tuberculosis (14).…”
Section: Significancementioning
confidence: 99%